(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
In this paper, we intend to explore the practices implemented by the heiresses of Luján during the late colonial period to access the portion of their inheritance that corresponded to them. The objective is to investigate the legal capacity of these men and women in relation to the construction of gender roles. We also seek to delve into the social uses of the justice system as a space for mediation and the resolution of conflicts concerning family, property, and inheritance. Thus, we focus on analyzing inheritance files from a gender perspective that inserts the issue of inheritance into the web of social relationships that sustained daily life and family reproduction, thereby enriching our knowledge of the social and cultural processes of the period and positioning gender relations as constitutive elements of this world.